2020
DOI: 10.1111/head.13765
|View full text |Cite
|
Sign up to set email alerts
|

Short and Mid‐Term Predictors of Response to OnabotulinumtoxinA: Real‐Life Experience Observational Study

Abstract: Objective To identify clinical predictors of excellent response to OnabotulinumtoxinA in patients with chronic migraine (CM) at 6 and 12 months of follow‐up. Background Clinical predictors of response to OnabotulinumtoxinA are scarce and have not been clearly reproduced and analyzed in detail. So far, predictors of response to OnabotulinumtoxinA assess response in general or good response, but not an excellent response. Methods Cohort study of patients attended in a specialized Headache Clinic in treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…Future studies should implement such comorbidities in their study design. In addition, different classifications of responsiveness should be considered, for example ≥25% vs. ≥50% response, excellent responders ( 56 ), full-length responders, or wearing-off responders ( 57 ). Moreover, the establishment of standardized protocols for treatment and for data collection during baseline and follow-up are necessary for reliable data analysis and bias exclusion ( 55 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should implement such comorbidities in their study design. In addition, different classifications of responsiveness should be considered, for example ≥25% vs. ≥50% response, excellent responders ( 56 ), full-length responders, or wearing-off responders ( 57 ). Moreover, the establishment of standardized protocols for treatment and for data collection during baseline and follow-up are necessary for reliable data analysis and bias exclusion ( 55 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of painkillers taken has never been linked specifically to a poor response to the BT-A, but this study revealed that patients with a higher AC at the baseline were more likely to experience a worsening in their migraine after the BT-A withdrawal (Figure 2). The overuse of painkillers may lower the activation threshold of the trigeminal nerve fibers: Buonvicino and co-workers discovered that the administration of indomethacin and eletriptan in rats for 1 month enhanced the expression of neuropeptides, their receptors, prostanoids, TRPV2, and TRPA1 in the rat trigeminal neurons (23,24). Moreover, chronic acetaminophen administration had proven to increase the expression of 5-HT2A receptors in the trigeminal ganglion of exposed rats, increasing trigeminal excitability (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, new studies have been published analysing the impact of daily headache in preventive treatment with OnabotA with discordant results. In 2020, a prospective cohort study concluded, after analysing 221 patients, that the patients with daily headache had 3.2 (95% CI: 1.33–7.68, p = 0.009) higher odds of 75% response rate to Onabot A at 6 months of treatment, which was not maintained at 12 months [ 34 ]. In our study, the presence of daily headache was also a predictive factor of a higher response to OnabotA treatment.…”
Section: Discussionmentioning
confidence: 99%